CLEANED X - Version 1.0.1: A user friendly Microsoft Excel tool to assess the environmental impacts of livestock production - Notenbaert, An Maria Omer; Paul, Birthe K.; Mukiri, Jessica; Birnholz, Celine A.; Koge, Jessica (2018)
The CLEANED (Comprehensive Livestock Environmental Assessment for Improved Nutrition, a Secured Environment and Sustainable Development along Livestock and Fish Value Chains) Excel tool is a rapid ex-ante environmental impact assessment tool that allows users to explore multiple impacts of developing livestock value chains. It models the impact of changes in the livestock production systems and value chains along several pathways on land use, productivity, economics, water impacts, greenhouse gas emissions and soil health. (2018-01-31)